Mass media discourse: a critical analysis research agenda - Abdullah, Faiz Sathi (Universiti Putra Malaysia Press, 2014)
In this article, I aim to revisit some key issues in approaches to research on mass media texts from a discourse analytical perspective and to present a rationale, as well as a Critical Discourse Analysis (henceforth, CDA) framework for analysis of mass media discourse. I then consider a number of areas of critical research interest in mass media discourse locally and elsewhere. Examples of actual CDA research on mass media discourse are reviewed in terms of topics of apparent popular interest among practitioners such as racist discourse in news reporting, language of globalization and neo-capitalism, and war news reporting, before listing methodological, as well as topical agenda by a major proponent in the field for further work. The article concludes that CDA’s multidisciplinary approach to research on mass media discourse helps reveal hidden socio-political issues and agenda in various areas of language as social practice and in doing so potentially empowers the individual and social groups.